Green Accounting Transparency, Organizational Image, and the Mediating Role of Maqasid Syariah Index on Public Trust in Zakat Management Organizations - Rahmat Daim Harahap; Muhammad Syukri Albani Nasution; Nurlaila (Fundamental and Applied Management Journal, 2026)
Public trust in Zakat Management Organizations (OPZ) is a fundamental prerequisite for sustainable Islamic philanthropic governance. This study examines the direct effects of green accounting transparency and organizational image on public trust in OPZ in North Sumatra Province, Indonesia, and tests the mediating role of the Maqasid Syariah Index (MSI). A quantitative causality design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.1. Primary data were collected from 171 respondents comprising muzaki, stakeholders, and OPZ partners through purposive sampling. Convergent validity was confirmed through standardized loading factors (SLF ≥ 0.70), Average Variance Extracted (AVE ≥ 0.50), Composite Reliability (CR ≥ 0.70), Cronbach's alpha, and rho_A. Discriminant validity was confirmed through HTMT ratios (< 0.90). Common method bias was assessed via full collinearity VIF at the construct level (all VIF < 3.3). Results indicate that green accounting transparency (β = 0.692, p < .001) and organizational image (β = 0.120, p = .002) significantly and positively influence public trust. MSI directly affects public trust (β = 0.145, p < .001) and significantly partially mediates the organizational image–public trust relationship (indirect β = 0.068, 95% CI [0.019, 0.117], p = .006). The green accounting–MSI–public trust mediation path was not significant (indirect β = 0.031, 95% CI [−0.003, 0.065], p = .074). The R² for public trust is 44.6%. These findings contribute to an integrative Islamic philanthropic accountability model anchored in legitimacy theory and stakeholder theory, with context-specific implications for North Sumatra OPZ governance.